Crystallization of Mn(II) and Cd(II) Complexes in A Water-Methanol System: Tartrate vs Nicotinamide Ligand Selectivity - Yuniar Ponco Prananto; Rafi Dwiasis Wibisono; Sasti Gona Fadhilah; Rachmat Tjahjanto; Darjito; Firsta Luthfiani Salsabila (The University of Mataram, 2022)
Ligand selectivity of tartrate vs nicotinamide in a water-methanol system has been observed in the crystallization of Mn(II) and Cd(II) complexes. These complexes were crystallized at room temperature by a layered solution technique using a water-methanol mixture solvent in a M(II):tartrate:nicotinamide (M = Mn, Cd) molar ratio of 1:1:2. Complexes of M(II)-nicotinamide and M(II)-tartrate were also prepared for data comparison. Analysis of the crystals by infrared spectroscopy, powder-X-ray diffraction and qualitative anion test showed that in a presence of both tartrate and nicotinamide, the Mn(II) forms neutral Mn(II)-tartrate hydrate complex, whereas the Cd(II) forms ionic Cd(II)-nicotinamide chloride complex. In the case of Mn(II) complex, tartrate tend to coordinate as ligand than the nicotinamide, although molar ratio of nicotinamide was doubled than that of tartrate ligand. In contrast, the neutral nicotinamide ligand is more predominant to coordinate in the Cd(II) complex than the anionic tartrate. The tartrate-nicotinamide ligand selectivity in the crystallization of Mn(II) and Cd(II) complexes is likely due to the use of tartrate salt as precursor and the choice of solvent mixture. In addition, powder-XRD analysis confirms that there was no indication of M(II)-tartrate and M(II)-nicotinamide that co-crystallized together at the same time by both metal ions.